Constraints on Wh-Question Formation in Gichuka - Peter, Muriungi Kinyua (Advances in Social Sciences Research Journal, 2015)
Ross (1976) argued that wh-movement is not unbounded. This paper investigated wh-question formation in Gichuka, and checked whether wh-movement is constrained/bounded by the complex NP constraint, the subject condition, the wh-island constraint and the coordinate structure constraint. The results indicate that wh-movement is constrained by these constraints except the complex NP constraint. This paper therefore is a contribution to the principles and parameters of universal grammar.